ERP-BIM Integration Impact on Post-Commissioning Payment Approval: A PLS-SEM Approach - I Gede Upeksa Negara; Asrul Sani (Sinkron : jurnal dan penelitian teknik informatika, 2026)
The construction industry continues to face inefficiencies in post-commissioning payment approval, resulting in delayed settlements, disputes, and increased project costs. Although Enterprise Resource Planning (ERP) and Building Information Modeling (BIM) have individually improved project management and information handling, their integrated use for financial process optimization remains insufficiently explored. This study aims to examine the effect of ERP-BIM integration on post-commissioning payment approval performance in construction projects and to identify the most influential determinants. A quantitative approach was employed using a structured questionnaire distributed to 150 construction professionals with direct experience in ERP and BIM implementation. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that System Integration Quality has the strongest effect on Data and Workflow Efficiency (β = 0.356; p < 0.001) and also significantly influences Payment Approval Performance (β = 0.301; p < 0.001). ERP Functional Maturity also demonstrates a strong positive effect on Data and Workflow Efficiency (β = 0.291; p < 0.001) and Payment Approval Performance (β = 0.274; p < 0.001). In addition, Data and Workflow Efficiency significantly affects Payment Approval Performance (β = 0.332; p < 0.001) and mediates the relationship between the exogenous constructs and the endogenous variable. The model explains 62.4% of the variance in Data and Workflow Efficiency and 71.3% of the variance in Payment Approval Performance. These findings indicate that ERP-BIM integration has substantial potential to improve financial workflow effectiveness and strengthen payment approval processes in construction projects.